On conceptual models for information seeking and retrieval research - Kalervo Jarvelin; T.D. Wilson (Information Research: An International Electronic Journal)
There are several kinds of conceptual models for information seeking and retrieval (IS&R). The paper suggests that some models are of a summary type and others more analytic. Such models serve different research purposes. The purpose of this paper is to discuss the functions of conceptual models in scientific research, in IS&R research in particular. What kind of models are there and in what ways may they help the investigators? What kinds of models are needed for various purposes? In particular, we are looking for models that provide guidance in setting research questions, and formulation of hypotheses. As a example, the paper discusses [at length] one analytical model of task-based information seeking and its contribution to the development of the research area.